Studies on Zooplankton Abundance, Species Diversity Seasonal Variation in path of the Godavari River, Nath Sagar Dam, Paithan, Aurangabad, Maharashtra, India (International Journal of Scientific Research in Science and Technology, 2024)
The zooplankton community structure were studied on monthly surveys throughout an annual cycle From January 2022 to December 2022 in Area path of Godavari River Nag Ghat in Paithan. Utilizing a conventional methodology, Zooplanktonic diversity and abundance were assessed. The seasonal cycles and population dynamics of the dominant species are described and discussed. The sample consists of moderate biodiversity of total zooplankton with 17 species belonging to Five taxonomic groups. Out of 17 species 6 belonged to Rotifera, 4 to copepod, 4 to cladocera, 2 to Ostracoda and 1 to Protozoa. Rotiferan species have showed a high magnitude of biodiversity in comparative to other zooplankton subgroups. The present study aims at providing a preliminary knowledge on the productivity and diversity of zooplanktons which is beneficial for the production of Fish.